Sistem Penilaian dalam Kurikulum 2013 dan Kurikulum Merdeka dalam Pengembangan Karakter Islami - Wahyuni, Ana Dwi; Aminun, Shiddiq; Ariyanto, Fikri; Isma, Muhamad (QuranicEdu: Journal of Islamic Education, 2025)
Assessment in education plays an important role in measuring the achievement of students' competencies. This study compares the 2013 Curriculum assessment system which emphasizes authentic competency-based assessment with the Independent Curriculum which uses flexible and holistic assessments according to individual needs. Using a qualitative descriptive approach and literature study, data was collected through the review of curriculum documents and reference sources related to the assessment system in the 2013 Curriculum and the Independent Curriculum. The analysis was carried out systematically to compare the principles, types, techniques, and implementation of assessments in the two curricula. This method allows for an in-depth understanding of the novelty and transformation of the assessment paradigm as well as the challenges of its application in the field. The results of the study show a significant novelty in the Independent Curriculum which provides greater space for teachers to design contextual and meaningful assessments, supporting the holistic development of students while increasing the capacity of teachers to understand learning objectives in depth. This study reinforces a new paradigm of assessment oriented to personal learning and islamic character development through the application of adaptive assessments. The novelty of this research lies in a comparative analysis that highlights the transformation of assessment as a tool for student development in a dynamic and inclusive learning context.